1987
DOI: 10.2190/tw3u-0886-q5ta-xhm4
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consciousness as the Monitoring of Cognitive States: A Theoretical Perspective

Abstract: Following a review of introspectionist, dualist, and functionalist theories of self-consciousness, a mind-brain monitoring theory is developed. According to monitoring theory, self-consciousness is one's tacit knowledge that one is experiencing sensations: in particular, that one is imaging sensations or that one is perceiving them. Such knowledge is the phenomenal consequence of neurally monitoring whether one's sensations are centrally innervated images or peripherally innervated percepts. As a corollary of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…According to Kunzendorf's theory of reality testing, the central innervation of normal imagery is neurally registered and tacitly experienced; and paradoxically, the central source of more vivid and percept-like imagery (with greater central innervation) is more easily registered and experienced [4]. Two previous experiments by Kunzendorf confirm that, within subject, normally attended percepts are immediately more discriminable from more percept-like images of greater vividness [5(Experiment 3), 6].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…According to Kunzendorf's theory of reality testing, the central innervation of normal imagery is neurally registered and tacitly experienced; and paradoxically, the central source of more vivid and percept-like imagery (with greater central innervation) is more easily registered and experienced [4]. Two previous experiments by Kunzendorf confirm that, within subject, normally attended percepts are immediately more discriminable from more percept-like images of greater vividness [5(Experiment 3), 6].…”
Section: Discussionmentioning
confidence: 96%
“…In recent studies of "reality testing", Kunzendorf has found that normal percepts are more easily discriminated from similar images of perceptual vividness than from similar images of lesser vividness [4][5][6]. However, in previous research on "reality monitoring", Johnson has found that memories of normal perception are more easily confused with detailed memories of similar imagery than with less accurate memories of similar imagery [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dixon's theory assumes that both attended and unattended stimuli are unconsciously perceived, but that only attended stimuli are subsequently represented as conscious sensations [1,2]. In contrast, Kunzendorf's theory assumes that both attended and unattended stimuli are consciously represented as sensations, but that only attended stimuli are accompanied by the self-awareness that one is perceiving them [3]. An experiment supporting this second theory is described, following the introduction of both approaches.…”
mentioning
confidence: 99%
“…Unlike Dixon's theory, Kunzendorf's theories of consciousness [19,20J and self-consciousness [3,20] assume that conscious sensations are necessary for perception, but that self-conscious monitoring of the perceptual state is not necessary. Kunzendorf's theory of consciousness [19-20J , a version of 'mindbrain identity' theory, assumes that conscious sensations are the phenomenal qualities of neural events necessary for perception: in particular, that visual sensations are the phenomenal qualities of retinal events, which are neurologically unique events necessary for the perception of optical structure.…”
mentioning
confidence: 99%